2005
DOI: 10.1080/00222930500392766
|View full text |Cite
|
Sign up to set email alerts
|

A redescription ofNeophilopterus tricolor(Burmeister, 1838) (Insecta: Phthiraptera: Ischnocera: Philopteridae) from the black storkCiconia nigra(L.) (Aves) with notes on its prevalence

Abstract: The accuracy of the Content should not be relied upon and should be independently verified with primary sources of information. Taylor and Francis shall not be liable for any losses, actions, claims, proceedings, demands, costs, expenses, damages, and other liabilities whatsoever or howsoever caused arising directly or indirectly in connection with, in relation to or arising out of the use of the Content. This article may be used for research, teaching, and private study purposes. Any substantial or systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…However, parasitic Mesostigmata were not found in the nests we examined. This is consistent with the observations of Lanzarot et al (2005), who found lice on 11 of the 50 nestlings of C. nigra that they examined in Spain, but no other parasites. A near or complete absence of blood-feeding parasitic Mesostigmata has also been reported for nests of the white-tailed eagle Fenďa & Lengyel 2007), and the white stork (Bloszyk et al 2005;Bajerlein et al 2006 (Krištofík et al , 2001(Krištofík et al , 2002Gwiazdowicz 2003a).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, parasitic Mesostigmata were not found in the nests we examined. This is consistent with the observations of Lanzarot et al (2005), who found lice on 11 of the 50 nestlings of C. nigra that they examined in Spain, but no other parasites. A near or complete absence of blood-feeding parasitic Mesostigmata has also been reported for nests of the white-tailed eagle Fenďa & Lengyel 2007), and the white stork (Bloszyk et al 2005;Bajerlein et al 2006 (Krištofík et al , 2001(Krištofík et al , 2002Gwiazdowicz 2003a).…”
Section: Discussionsupporting
confidence: 81%
“…The black stork and other species of Ciconia are attacked by a variety of ectoparasites, including lice (Ezealor 1985;Martin Mateo 1988;Z lotorzycka 1990;Lanzarot et al 2005;Dik & Uslu 2006), parasitic Astigmata (Fain & Laurence 1986;Chen & Fan 2003), quill mites (Bochkov & Mironov 1999), ticks (Ezealor 1985;Dik & Uslu 2006) and feather mites (Perez & Atyeo 1992;Janssen et al 2004). It is possible that predatory mites play a role in nest hygiene by feeding on these parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Ischnocera lice can affect host thermoregulation and induce feather breakage, reducing host fitness through the energetic consequences of that damage. Stress is also an indirect effect to the affected host [10]. Lice specimens found in this report's black stork had four marginal temporal setae of approximately the same length but the last one was several times shorter, thus being identified as N. tricolor.…”
Section: Discussionmentioning
confidence: 64%
“…In the present work, three different parasites of C. nigra were observed during necropsy of an adult specimen. Genus Neophilopterus (Ischnocera: Philopteridae) has already been described in black storks from Spain [10]. Ischnocera lice can affect host thermoregulation and induce feather breakage, reducing host fitness through the energetic consequences of that damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation